The Red Beds series in the Erta Ale segment, North Afar. Evidence for a 6 Ma-old post-rift basin prior to continental rupturing - Le Gall, B.; Leleu, S.; Pik, R.; Jourdan, Fred; Chazot, G.; Ayalew, D.; Yirgu, G.; Cloquet, C.; Chauvet, F. (Elsevier BV, 2018)
The Erta Ale rift segment, North Afar, is regarded as the most mature rift part within the entire Afar rift system. Very little is known about its deformation history because of limited exposures of geological records in its inner floor, except volcanics of the Erta Ale chain, and the poorly-known Red Beds series along the flanks of the depression. An integrated study, combining sedimentological, geochemical, 40Ar-39Ar radiometric and tectonic approaches, has been devoted to Red Beds series flanking the depression to the SW. Our new results allow to argue that (1) the >300 m-thick Red Beds exposed section comprises alluvial deposits that enclose (2) basaltic lavas and related sill intrusions that both yield ~6 Ma 40Ar-39Ar ages and display similar geochemical affinities, (3) the Red Beds series locally overlap unconformably basement bounding terrains, and (4) are involved in a limited number of low-displacement normal faults that recorded a modest amount of extension (<6%), (5) isotope contents of Red Beds volcanics indicate crustal contamination, without any contribution of the Afar plume, by contrast to the younger Erta Ale magmatism which represents the more recent Afar-plume related event in the Erta Ale segment. Combining these results leads us to regard the Red Beds series as part of an alluvial basin that post-dated a major rift event to which are attributed to (1) the present-day Ethiopian fault-scarp, (2) a concealed sedimentary depocenter at depth in its hanging wall, and (3) prominent crustal thinning. Riftward migration and axial focusing of strain during Miocene-Present times is also argued, while later flexuring of the entire Red Beds basin is assigned to magmatic loading during the axial emplacement of the Erta Ale volcanic chain. Lastly, emphasis is put on the large-scale segmentation of the Afar system into the tectonically-accreted Erta Ale rift segment to the north, and the magmatically-accreted Central segment to the south.